Title: efficacy of a food parenting intervention for mothers with low income to reduce preschooler's solid fat and added sugar intakes: a randomized controlled trial - Jennifer O. Fisher; Elena L. Serrano; Gary D. Foster; Chantelle N. Hart; Adam Davey; Yasmeen P. Bruton; Linda Kilby; Lisa Harnack; Karen J. Ruth; Alexandria Kachurak; Hannah G. Lawman; Anna Martin; et al. (BMC, 2019)
Abstract Background Few interventions have shown efficacy to influence key energy balance behaviors during the preschool years. Objective A randomized controlled trial (RCT) was used to evaluate the efficacy of Food, Fun, and Families (FFF), a 12 week authoritative food parenting intervention for mothers with low-income levels, to reduce preschool-aged children's intake of calories from solid fat and added sugar (SoFAS). Methods Mothers were randomly assigned to receive FFF (n = 59) or to a delayed treatment control (n = 60). The primary outcome was children's daily energy intake from SoFAS at the end of the 12 week intervention, controlling for baseline levels, assessed by 24-h dietary recalls. Secondary outcomes included children's daily energy intake, children's BMI z-scores, and meal observations of maternal food parenting practices targeted in FFF (e.g. providing guided choices). Results Participating mothers were predominantly African American (91%), with 39% educated beyond high school and 66% unemployed. Baseline demographics and child SoFAS intakes did not differ by group. Lost to follow-up was 13% and did not differ between groups. At post-intervention, FFF children consumed ~ 94 kcal or 23% less daily energy from SoFAS than children in the control group, adjusting for baseline levels (307.8 (95%CI = 274.1, 341.5) kcal vs. 401.9 (95%CI = 369.8, 433.9) kcal, FFF vs. control; p < 0.001). FFF mothers also displayed a greater number of authoritative parenting practices when observed post-intervention with their child at a buffet-style meal (Wilcoxon z = − 2.54, p = 0.012). Neither child total daily energy intake nor BMI z-scores differed between groups post-intervention. Conclusions Findings demonstrate the initial efficacy of an authoritative food parenting intervention for families with low-income to reduce SoFAS intake in early childhood. Additional research is needed to evaluate longer-term effects on diet and growth. Trial registration Retrospectively registered at ClinicalTrials.gov: #NCT03646201.